Analysis of the microbiological quality of water in public schools in the city of Belém, State of Pará (PA) (Research, Society and Development, 2024)
The general objective of the present study was to analyze the microbiological quality of water from drinking fountains and taps in ten public schools, in order to establish whether they are suitable for consumption according to current legislation. 100 ml of sample were collected for analysis of each established point and these were sent to the clinical analysis laboratory, at Faculdade Faci Wyden, where qualitative analyzes of total coliforms and Escherichia Coli were carried out, using the colilert enzymatic chromogenic substrate method. immediately after application of the reagent and incubation for 48 hours at 37 °c, a yellowish color was observed in a significant part of the samples, demonstrating the presence of total coliforms. however, the presence of e. coli was not detected in any of the samples analyzed, as they did not show fluorescence under ultraviolet light. in summary, water contamination represents a significant challenge to health and quality of life. therefore, to mitigate the negative effects of water pollution, it is essential to adopt proactive prevention strategies.